2015
DOI: 10.1523/jneurosci.5137-14.2015
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of the Intracortical LFP during Action Execution and Observation

Abstract: The activity of mirror neurons in macaque ventral premotor cortex (PMv) and primary motor cortex (M1) is modulated by the observation of another's movements. This modulation could underpin well documented changes in EEG/MEG activity indicating the existence of a mirror neuron system in humans. Because the local field potential (LFP) represents an important link between macaque single neuron and human noninvasive studies, we focused on mirror properties of intracortical LFPs recorded in the PMv and M1 hand regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
19
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(21 citation statements)
references
References 48 publications
2
19
0
Order By: Relevance
“…As described for the mu rhythm, beta ERD also occur during both movement execution (Ofori et al, 2015 ) and observation (Zarka et al, 2014 ; Cevallos et al, 2015 ; Babiloni et al, 2016 ). This evidence was recently reinforced by LFP recordings in the monkey showing modulation of beta power in M1 and premotor cortex during action execution and observation (Waldert et al, 2015 ).…”
Section: Beta Oscillationmentioning
confidence: 73%
“…As described for the mu rhythm, beta ERD also occur during both movement execution (Ofori et al, 2015 ) and observation (Zarka et al, 2014 ; Cevallos et al, 2015 ; Babiloni et al, 2016 ). This evidence was recently reinforced by LFP recordings in the monkey showing modulation of beta power in M1 and premotor cortex during action execution and observation (Waldert et al, 2015 ).…”
Section: Beta Oscillationmentioning
confidence: 73%
“…These differences between studies could be due to the disparity of cortical area sampled in the SEEG study (disjoint sites, 62-92 deep electrode) vs. the ECoG study (continuous sites, 112 contacts with 7.1 mm inter-electrode distance). A study of sustained hand grasp in non-human primates showed distinct peaks of gamma modulations at both grasp onset and offset (Waldert et al, 2015). Others also briefly mentioned the presence of biphasic peaks of ERS in human ECoG during hand grasp (Flint et al, 2017).…”
Section: Temporal Dynamics Of Lfb-erd and Hfb-ersmentioning
confidence: 99%
“…Although the primary motor cortex (M1) is not classically considered an integral part of the core parietofrontal MNS (Iacoboni, ; Rizzolatti & Sinigaglia, ), there is accumulating evidence for M1 activity during action observation. Electrophysiological studies in monkeys demonstrated the existence of cells with mirroring properties in this region (Dushanova & Donoghue, ; Tkach et al., ; Vigneswaran et al., ; Waldert, Vigneswaran, Philipp, Lemon, & Kraskov, ). TMS studies further support the role of M1 in observational learning.…”
Section: Discussionmentioning
confidence: 99%